2017
DOI: 10.1016/j.soscij.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

School context and American Indian substance use

Abstract: The present study extends prior research exploring the role of school contextual factors in predicting individual adolescent substance use by examining how a school's racial composition is associated with American Indian adolescent tobacco and marijuana use. Using a subsample of 523 American Indian students from the restricted use Add Health data, we consider both individual and school contextual factors across 99 schools. Our results suggest that a school's racial composition is associated with individual tob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…Several of the included studies showed the importance of school resources to protect AI/AN youth against substance misuse. Schools with more resources were seen to be concomitant with lower substance misuse among AI/AN youth (Eitle et al, 2017). The more the AI/AN youth were connected to the school by both in-school and after-school activities, including involvement with teachers, the more resilient against substance misuse they were.…”
Section: Microsystem-level Factorsmentioning
confidence: 92%
See 4 more Smart Citations
“…Several of the included studies showed the importance of school resources to protect AI/AN youth against substance misuse. Schools with more resources were seen to be concomitant with lower substance misuse among AI/AN youth (Eitle et al, 2017). The more the AI/AN youth were connected to the school by both in-school and after-school activities, including involvement with teachers, the more resilient against substance misuse they were.…”
Section: Microsystem-level Factorsmentioning
confidence: 92%
“…School. Connectedness to school increased resilience against substance misuse (Eitle et al, 2017;Friese et al, 2015;Moon et al, 2014;Turanovic & Pratt, 2017). Positive school adjustment, highlighted by AI/AN youth's positive attitude regarding school, had increased resilience against substance misuse (Greenfield et al, 2017;Sittner, 2017).…”
Section: Microsystem-level Factorsmentioning
confidence: 98%
See 3 more Smart Citations